Konsep Tasawuf Perspektif Imam Nawawi: Studi Tentang Interpretasi Hadis Sufistik dalam Kitab Al-Arba’in An-Nawawiyyah - suprayitno, muhammad aji; Agus Santoso (Qolamuna : Jurnal Studi Islam, 2024)
This research investigates Imam Nawawi's views on Sufism through an analysis of the interpretation of Sufistic hadith contained in his work, "Al-Arba'in An-Nawawiyyah." Sufism is a branch of Islam that pursues a deeper understanding of God, spiritual life, and morality. In this research, we explore how Imam Nawawi, who is famous for his firm understanding of hadith and fiqh, understands and conveys the concepts of Sufism in his work. This research method includes analysis of the Sufi hadith texts included in "Al-Arba'in An-Nawawiyyah," with a focus on the way Imam Nawawi interpreted and explained them. This research also considers the historical and cultural context in which Imam Nawawi lived, which may have influenced his understanding of Sufism. It is hoped that the results of this research will provide a better understanding of the concept of Sufism from Imam Nawawi's perspective, as well as its contribution in embracing the spiritual dimension of Islam. This can also help in understanding the complexity and diversity of Islamic thought, as well as how various schools of thought in Islam can coexist and synergize in the development of Muslim spirituality and morality. While the hadith that have Sufism values in the book al-Arbain an-Nawawiyyah include: intention, ihsan, wara’, be patient, routine, dzikir, andzuhud. Keywords : Sufism, Imam Nawawi, Sufistic Hadith, Al-Arbain An-Nawawiyyah.